Epidemiology of Nontuberculous Mycobacteria in Tuberculosis suspects, Southwest of China, 2017-2022 - Wang, Dong-Mei; Liu, Hong; Zheng, Yong-Li; Xu, Yuan-Hong; Liao, Yi (Frontiers in Cellular and Infection Microbiology, 2023)
Objectives This study summarizes the epidemiological characteristics, species distribution, and drug sensitivity of clinical nontuberculous mycobacteria (NTM) isolates at the Public Health Clinical Center of Chengdu, China, from January 2017 to December 2022. Methods We retrospectively analyzed data from patients with clinically isolated NTM strains. Chi-square analysis assessed the rate of Mycobacterium strain isolation over 6 years. Results The number of samples tested for Mycobacterium tuberculosis (MTB) and/or NTM increased each year, while MTB detection decreased and NTM detection rose significantly each year (P=0.03). The average age of NTM patients was 51 ± 17.53 years, with a 14.1% HIV infection rate. The predominant isolates were Mycobacterium avium-intracellulare (MAC) and M. chelonae/M. abscessus, with 96.4% of cases being of Han ethnicity. Amikacin, moxifloxacin, and clarithromycin were effective against M. avium and M. intracellulare; linezolid, amikacin, and cefoxitin were effective against M. chelonae/M. abscessus. Over 90% of NTM cases originated from the respiratory tract. Conclusion The NTM isolation rate in Southwest China has risen in recent years, primarily among elderly patients with a high HIV co-infection rate. The main NTM isolates were MAC and M. chelonae/M. abscessus. Amikacin, moxifloxacin, clarithromycin, and linezolid exhibited strong antibacterial activity against SGM, while amikacin and linezolid displayed relatively better antibacterial activity against RGM. The prevalence of NTM infection may be positively associated with regional economic development and health conditions.